2‐Aminoalkylgold Complexes: The Putative Intermediate in Au‐Catalyzed Hydroamination of Alkenes Does Not Protodemetalate. Issue 38 (27th May 2022) - Gubler, Joël; Radić, Mitar; Stöferle, Yannick; Chen, Peter
Abstract: Au‐catalyzed hydroamination proceeds well for alkynes but not alkenes. We report gas‐phase binding energies of alkenes and alkynes to a cationic Au center, which indicate that differences in binding are not the origin of the disparate chemical behavior. We further report the synthesis and characterization of 2‐aminoalkylgold complexes, which would be the intermediates in a hypothetical Au‐catalyzed hydroamination of styrene. The reactivity of the well‐characterized and isolable complexes reveals that protonation or alkylation of the 2‐aminoalkylgold complexes results in amine elimination in solution, and in the gas phase, indicating that the failure of Au‐catalyzed alkene hydroamination derives from a non‐competitive protodeauration step. We analyze possible transition states for the protodeauration, and identify an insufficiently strong Au‐proton interaction as the reason that the transition states lie too high in energy to compete. Abstract : 2‐Aminoalkylgold(I) complexes, the putative intermediates of Au(I)‐catalyzed hydroamination of alkenes, were isolated and characterized. Upon titration with different acids, the complexes underwent elimination to alkenes. This behavior was further observed in the gas phase following protonation. Together with CID experiments, the results indicate that the origin of the poor reactivity of alkenes in hydroamination reactions, lies in the uncompetitive protodeauration step.